2019
DOI: 10.1016/j.adolescence.2019.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction trajectories of junior high school students in poverty: Exploring the role of self‐efficacy and social support

Abstract: Introduction: Adolescents' evaluation of overall life in response to adverse life circumstances may depend on the features of events as well as the resources of the youngsters, but there is a lack of research examining whether these factors relate to life satisfaction trajectories from early adolescence to late adolescence (ranging from age 12 to 19). This study analyzes whether controllable negative life events, internal resources, (e.g., self-efficacy) and external resources, (e.g., three sources of social s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
1
10
0
5
Order By: Relevance
“…However, some studies have reported that adolescents’ self-efficacy of shows a downward trend with time (Burger & Samuel, 2017). This is consistent with a 2-year longitudinal study of junior high school students (Jhang, 2019). Adolescents’ self-efficacy is closely related to their resilience (Sagone & Caroli, 2013; Sagone et al, 2020).…”
Section: Introductionsupporting
confidence: 91%
“…However, some studies have reported that adolescents’ self-efficacy of shows a downward trend with time (Burger & Samuel, 2017). This is consistent with a 2-year longitudinal study of junior high school students (Jhang, 2019). Adolescents’ self-efficacy is closely related to their resilience (Sagone & Caroli, 2013; Sagone et al, 2020).…”
Section: Introductionsupporting
confidence: 91%
“…Previous studies have demonstrated that social support can buffer the impact of NLEs on depression, anxiety, and other psychological problems (24,28,55). Social support from the school, family, and other environments is a positive predictor of adolescents' QoL (29,56).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most effective means of coping with challenging life events is perceived social support (PSS), which determines a person's health and well-being [27,28]. The positive relationship between social support and LS has been repeatedly reported, but mostly aimed at students, the elderly or disease-related population [29][30][31]. A small number of studies discussed the impact of social support on pregnant women's LS.…”
Section: Introductionmentioning
confidence: 99%